Psychology of learning and behavior - Schwartz, Barry, 1946-; Robbins, Steven J. (New York : W. W. Norton, 1995)
Human nature, science and behavior theory. Single event learning. Pavlovian conditioning. Pavlovian conditioning. Operant conditioning. Aversive control of behavior. The maintenance of behavior. Stimulus control of operant behavior. Interactions between Pavlovian and operant conditioning.
Keywords: Psychology; Conditioned response; Conditioned response; Behaviorism (Psychology)